2021
DOI: 10.3390/ijerph18020509
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Urban Natural Environments on Preference and Self-Reported Psychological Restoration of the Elderly

Abstract: The world is facing the challenge of aging populations. Urban natural environments, including green spaces and blue spaces, have been demonstrated to have great benefits to the mental restoration of the elderly. However, the study of the specific characteristics of urban environments that are popular and the most restorative for the elderly is still lacking. Photo elicitation as visual stimuli was utilized to explore the differences in preference and psychological restoration of the elderly through the percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 56 publications
3
25
0
2
Order By: Relevance
“…Moreover, serene and nature were placed in the middle, indicating that artificial lake spaces were relatively calm, clean, and natural. This result was consistent with the previous study, which showed that blue spaces like open artificial lake spaces could provide tranquility to people (Gao et al, 2019;Qiu et al, 2021). On the one hand, water can absorb noise to create a better soundscape; further, human activity sounds were concentrated densely on the water bank, resulting in a decrease of tranquility (Dinda and Ghosh, 2021).…”
Section: Representation Of the Eight Psds In Blue Spacesupporting
confidence: 92%
“…Moreover, serene and nature were placed in the middle, indicating that artificial lake spaces were relatively calm, clean, and natural. This result was consistent with the previous study, which showed that blue spaces like open artificial lake spaces could provide tranquility to people (Gao et al, 2019;Qiu et al, 2021). On the one hand, water can absorb noise to create a better soundscape; further, human activity sounds were concentrated densely on the water bank, resulting in a decrease of tranquility (Dinda and Ghosh, 2021).…”
Section: Representation Of the Eight Psds In Blue Spacesupporting
confidence: 92%
“…Ayala-Azcárrag et al 2019;Bringslimark et al 2009;Hedblom et al 2019;Kaplan and Kaplan 1989;Kuo and Sullivan, 2001;Scopelliti et al 2018;Ulrich 1984;1986;White and Gatersleben 2011). A number of studies based on the Biophilia hypothesis (Wilson 1984), Attention Restoration Theory (ART) (Kaplan and Kaplan 1989) and the Stress Reduction Theory (Ulrich 1983) provided empirical evidence that wildlife has multiple benefits for human health and well-being (Berto 2005;Hartig et al 2014;Jarvis et al 2020;Laumann et al 2001;Qiu et al 2021). The importance of nature for people is also taken into account by programs and strategies related to urban policy (Hoyle et al 2017;Evensen et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation for this result may be that moderate complexity is most preferred (Ulrich, 1986), low complexity is perceived as monotonous and boring, while high complexity confusing (van den Berg & van Winsum-Westra, 2010). Moderate complexity correspondingly induces psychological restorative benefits because of the close ties between preference and mental restoration (Qiu et al, 2021; Wang & Zhao, 2020). Although no literature concretely defines moderate complexity, the videos with two or more landscape elements used in this study may have a high complexity due to the fact that respondents experience a path landscape within 2 min or 150 m travel, and the videos with one element possess a low complexity.…”
Section: Discussionmentioning
confidence: 99%